Social inequalities in the misbelief of chloroquine’s protective effect against COVID-19: results from the EPICOVID-19 study in Brazil - Bruno Pereira Nunes; Inácio Crochemore-Silva; Grégore I. Mielke; Luis Paulo Vidaletti; Marilia Arndt Mesenburg; Mariangela Freitas da Silveira; Pedro C. Hallal (PLoS ONE, 2026)
Objectives This study aimed to assess the dissemination of anti-science messages regarding COVID-19 in Brazil, specifically examining how social inequalities contributed to the misconception that chloroquine has a protective effect against the virus. Study design Three countrywide population-based studies were conducted in 2020 (May 14–21, June 4–7, and June 21–24), including 133 Brazilian cities (N = 74,077). Methods Participants (≥20 years old) were asked whether they believed in chloroquine’s protective effect against infection with the SARS-CoV-2 virus (no/yes/don’t know). “Yes” and “don’t know” answers were considered misconceptions (effect of denialism). A jeopardy index score was calculated to assess cumulative social deprivation based on sex, race and ethnicity, and socioeconomic variables. Descriptive analysis and inequality measures (Slope Index of Inequality – SII; and Concentration Index) were used to evaluate the association between believing in chloroquine’s protective effect against COVID-19 and the jeopardy index. Multinomial logistic regression was used in the unadjusted and multivariable analysis. Results Overall, 47.6% of participants either believed that chloroquine prevented COVID-19 or stated, “I don’t know.” Marginalized racial and ethnicity groups, those with low education level, and those with low socioeconomic status were more likely to erroneously believe that chloroquine prevented COVID-19. The chance of lack of knowledge (Don’t know) was higher (Odds Ratio: 2.57,CI95% 2.21; 2.99) among women, Black/Brown/East Asian/Indigenous, and among those in the lowest education level and wealth quartiles compared to men, white individuals, and those in the highest education and wealth quartiles. Absolute and relative inequalities were observed according to the jeopardy index. The highest absolute inequality was observed for the category “I don’t know” (SII = −15.1). Conclusions Misbelief in chloroquine’s protective effect against SARS-CoV-2 was high in Brazil. People with greater social vulnerability were more likely to wrongly believe that chloroquine prevented COVID-19.